PERAN KEPEMIMPINAN DALAM MENDORONG IKLIM ORGANISASI YANG ADAPTIF DI UPTD SDN 2 BATI-BATI - Meldayani, Sri; Oktavia, Amalia; Purtama, Dian; Purnamasari, Indah; Arief Prasetya, Muhammad; Suriansyah, Ahmad; Purwanti, Ratna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of leadership in fostering an adaptive organizational climate at UPTD SDN 2 Bati-Bati. This research uses a qualitative approach with a field research design. The subjects of this study include the principal, teachers, and educational staff. Data were collected through observation, in-depth interviews, and documentation. The validity of the data was ensured through source and technique triangulation. The results indicate that the principal applies leadership practices that lead to a transformational approach, characterized by participative communication, motivation, and support for innovation. This leadership contributes to the formation of an adaptive organizational climate marked by openness, collaboration, and responsiveness to change. Thus, leadership plays a crucial role in enhancing the adaptability of educational organizations.